The sequence context of the initiation codon in the encephalomyocarditis virus leader modulates efficiency of internal translation initiation. - Davies, M V (1992)
Translation initiation on poliovirus and encephalomyocarditis virus (EMCV) mRNAs occurs by a cap-independent mechanism utilizing an internal ribosomal entry site (IRES). However, no unifying mechanism for AUG initiation site selection has been proposed. Analysis of initiation of mRNAs translated in vitro has suggested that initiation of poliovirus mRNA translation likely involves both internal binding of ribosomes and scanning to the first AUG which is in a favorable context for initiation. In contrast, internal initiation on EMCV mRNA may not utilize scanning, since ribosomes bind directly or very close to the initiation codon AUG-11. We have studied in vivo the sequence requirements for internal initiation around the EMCV initiation codon, both in monocistronic and in dicistronic mRNAs. Our studies show that the upstream AUG-10 is normally not used and that there is no specific sequence requirement for nucleotides between AUG-10 and AUG-11. However, the sequence context of AUG-11 does influence the efficiency of initiation at AUG-11. Efficient IRES-mediated internal initiation at AUG-11 exhibits a requirement for an adenine in the -3 position, similar to cap-dependent initiation. These results support a model for internal initiation on EMCV mRNA in which scanning starts at or near AUG-11. Although initiation primarily occurs at AUG-11, initiation at multiple downstream AUG codons can be detected. In addition, a poor sequence context around AUG-11 results in increased initiation at one or more downstream AUG codons, indicative of leaky scanning or jumping by the ribosome from AUG-11 mediated by the EMCV IRES.